Pengaruh Brand Satisfaction, Brand Trust, Dan Brand Experience Terhadap Brand Loyalty Merek Eiger (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Mochamad Firli Ardiansyah; Nurhidayah Nurhidayah; Sulton Sholehuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the influence of brand satisfaction, brand trust and brand experience on Eiger brand loyalty. The independent variables used are brand satisfaction, brand trust and brand experience, while the dependent variable is brand loyalty. The sample used in this study was 90 respondents who were students of Islamic University of Malang who were customers of Eiger brand products. Data collection method using questionnaires. The data analysis used in this study used validity and reliability tests, normality tests, analysis multiple linear regression, multicollinearity test, heteroscedasticity test, t test and R2 coefficient of determination. The results of this study show that brand satisfaction has a positive and significant effect on Eiger brand loyalty, brand trust has a positive effect and significant to the brand loyalty of the Eiger brand, and brand experience has a positive and significant effect on the brand loyalty of the Eiger brand.  Keywords: Brand Satisfaction, Brand Trust, Brand Experience, Brand Loyalty, Eiger Brand.